Fingerprint Voting System For Election Commission In Malaysia - Gurdial Singh, HavinderSingh (IRC, 2019)
The developing phenomenon of digital violations has particularly made opposing impact similarly as conveying unlimited risks affecting local's regular daily existences, authoritative and business information systems. Because of the ascending of advanced security threats that have provoked extended digital wrongdoing rates and vulnerabilities rates, the architect has illustrated a verified structure that remembers the true objective to control the administrative race framework. Presently, there were a couple of current electronic casting a ballot systems that completed in different countries, for instance, India, Estonia and Hungary stand up to a noteworthy issue as the structures has been seen as a prime concentration for security strikes.